#1**+1 **

-3x^{2} + 4x + 1 = 16x + 13

Add 3x^{2} to both sides of the equation.

4x + 1 = 3x^{2} + 16x + 13

Subtract 4x from both sides of the equation.

1 = 3x^{2} + 12x + 13

Subtract 1 from both sides of the equation.

0 = 3x^{2} + 12x + 12

Now we can use the quadratic formula, with a = 3, b = 12, and c = 12, to solve for x.

\(x = {-12 \pm \sqrt{12^2-4(3)(12)} \over 2(3)} \\~\\ x = {-12 \pm \sqrt{144-144} \over 6} \\~\\ x = {-12 \pm \sqrt{0} \over 6} \\~\\ x = {-12\over 6} \\~\\ x = -2\)

hectictar
May 23, 2017